Geopolymer as a new landfill soil liner design / Atiqah Najwa Zainuddin ... [et al.] - Zainuddin, Atiqah Najwa; Mukri, Mazidah; Che Lat, Diana; Yusof, Nurul Ain Umaiban; Che Hassan, Asmawati (2022)
The study investigates a green technology geopolymer as an additive in enhancing the properties of landfill soil liner. Soil liners are used to contain waste in modern landfills. Geopolymer can be considered the key factor that could enhance laterite's properties in the performance of hydraulic conductivity. In this study, geopolymer paste consists of palm oil boiler ash mixed with an alkaline solution of sodium hydroxide and sodium silicate. Boiler ash is another industrial waste product from the combustion of coal. Laterite mix was mixed with different percentages of boiler ash-based geopolymer to improve the properties of soil liner application. This research aims to determine the optimum percentage of geopolymer mixed with laterite as an additive and reduce the value of hydraulic conductivity. Based on results, the increases in geopolymer content are associated with a decrease in hydraulic conductivity, leading to a significant reduction in hydraulic conductivity. An empirical model was successfully developed from this study. The empirical model in predicting hydraulic conductivity, k, was developed as alternative guidelines for engineers to design landfill soil liners without conducting laboratory testing that takes a long time and can reduce the cost and time.